2021
DOI: 10.1111/jch.14409
|View full text |Cite
|
Sign up to set email alerts
|

The effect of frailty on the 24‐hour blood pressure pattern in the very elderly

Abstract: Frailty plays a crucial role in the management of hypertension in the very elderly and has a strong association with cardiovascular diseases. Nevertheless, its influence on the 24‐hour blood pressure pattern, including elevated asleep systolic blood pressure (BP) and the lack of BP fall during sleep (non‐dipping) has not been explored in a population above 80 years. Patients older than 80 years were classified into frail or robust subtypes by the five item frailty phenotype criteria. All participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…A similar study conducted in this context revealed a statistically significant association between non-dipping blood pressure and daytime systolic blood pressure (SBP) load among non-dippers and reverse dippers. This consistency across different socioeconomic settings underscores the robustness and generalizability of the observed relationship between non-dipping blood pressure and daytime SBP load, regardless of the economic context [23]. The findings show further consistency with study that were done in high income countries, Spain and Italy, whose findings revealed an association of daytime systolic blood pressure (SBP) load level to development of non-dipping BP [21,22].…”
Section: Discussionsupporting
confidence: 78%
“…A similar study conducted in this context revealed a statistically significant association between non-dipping blood pressure and daytime systolic blood pressure (SBP) load among non-dippers and reverse dippers. This consistency across different socioeconomic settings underscores the robustness and generalizability of the observed relationship between non-dipping blood pressure and daytime SBP load, regardless of the economic context [23]. The findings show further consistency with study that were done in high income countries, Spain and Italy, whose findings revealed an association of daytime systolic blood pressure (SBP) load level to development of non-dipping BP [21,22].…”
Section: Discussionsupporting
confidence: 78%
“…As for the influence of frailty on the 24-h BP pattern, it has been explored in a short study with population above 80 years. In this study, frail patients had higher nocturnal systolic BP, and were independently associated with higher risk of nondipping and reduced nighttime systolic BP fall [29].…”
Section: Frailtymentioning
confidence: 54%
“…In older hypertensive patients, one of the age-associated BP abnormalities could be the loss of nocturnal BP dip, therefore, the proportion of nondippers tends to increase compared with that of in younger subjects [26]; in some studies, up to 43% of elderly hypertensive patients could have a nocturnal BP elevation [28], this is even more frequent in elderly frail subjects [29]. These changes in circadian pattern, among elderly hypertensive patients, are associated with an increased cardiovascular risk.…”
Section: Nocturnal Hypertension and Nondipping Patternmentioning
confidence: 99%
“…Other series showed lower BP values in frail patients with increased presence of comorbidities, malnutrition, and overtreatment [ 34 , 35 ]. Frailty was associated with higher risk of non-dipping and reduced night-time systolic BP fall in a small study evaluating 24-h ambulatory BP, possibly indicating an effect of frailty on sleep quality and mobility, vascular endothelial dysfunction or impairment in the autonomic system [ 36 ]. However, differences in the BP pattern may simply reflect a selection bias of evaluated patient populations; in particular, low BP would appear in the context of severely frail patients as a marker of reduced functional reserve and poor baseline health [ 37 ].…”
Section: Hypertension and Frailtymentioning
confidence: 99%